Students’ Perception of Google Translate in Improving Writing Skill - Yoana G. P. Lengari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2023)
The aim of this study is to determine the perception on using Google Translate in the third semester of Engineering Students of Akademi Maritim Nusantara Cilacap to improve their writing skill. Ten students were selected as the research participants for this study. The data for this study is obtained by experimental study and questionnaire. The questions consist of the students’ perception in using Google Translate to help them improve their writing skill in EFL and their perception of Google Translate for improving their writing. By using descriptive-qualitative analysis, it is identified that the respondents produce better writing by utilizing Google Translate to help them with their writing task. The study also shows that although there are some disadvantages in using Google Translate, most respondents agree that there are more advantages to it in helping them improve their writing skill. In conclusion, this study reveals that there is positive perception in using Google Translate to improve writing skill and it is useful to improve the students’ writing skill.